Causal effects of dietary calcium, zinc and iron intakes on coronary artery disease in men: G-estimation and inverse probability of treatment weighting (IPTW) analyses. (April 2021) - Basnet, Til Bahadur; G.C., Srijana; Basnet, Rajesh; Neupane, Bidusha; Thapa, Goma
Summary: Background & aims: Dietary minerals have significant effects on the risk of cardiovascular disease. However, the results of previous studies were not uniform across different countries. The current study aims to determine the causal effects of dietary calcium, zinc, and iron intakes on coronary artery disease (CAD) among Nepalese men. Methods: A matched case–control study was carried out at Shahid Gangalal National Heart Center. Dietary intakes of 466 male participants over the past 12 months were evaluated using a semi-quantitative customized food frequency questionnaire. G-estimation and inverse probability treatment weighting (IPTW) analyses were performed to determine the causal odds of CAD due to dietary calcium, zinc, and iron intakes. Results: Daily dietary calcium, zinc, and iron intakes were categorized into two groups: less than versus more than the median value and less than versus equal or more than recommended daily allowance (RDA). In G-estimation, dietary calcium intake was inversely associated with CAD in both medians (OR: 91; 91%CI: 0.86, 95) and RDA categories (OR: 0.88: 95%CI: 0.84, 0.97). However, in IPTW analysis, only median calcium intake was significantly associated with CAD (OR: 7; 91%CI: 0.5, 98). We observed a significant inverse association of equal or more than RDA of dietary zinc intake with CAD (OR: 0.91: 95%CI: 0.87, 0.96 in G-estimation, OR: 0.73: 95%CI: 0.66, 0.82 in IPTW); however, more than median dietary zinc intake showed inverse but not significant association with CAD in both analyses. Dietary iron intake was inversely but not significantly associated with CAD in G-estimation in both groups. Nevertheless, in IPTW analysis, equal or more than RDA iron intake was significantly positively (OR: 1.4; 95%CI: 1.14, 1.73) related to CAD. Conclusions: A significant inverse association of dietary zinc intake above RDA indicates the potential protective effect of higher dietary zinc against CAD. However, causal odds of CAD are inconsistent across the median or RDA of calcium and iron intakes. Therefore, cohort and randomized clinical trial studies with a large sample size are recommended to substantiate these nutrients' causal link with CAD development in the Nepalese population.